Gender specificities of cardiovascular risk factors in students - A. E. Bragina (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To study gender differences in the prevalence of cardiovascular risk factors (RF) among higher education medical students.Material and methods. We examined 74 men and 143 women studying at higher education medical institution. Behavioral and biological RF were evaluated. Psychoemotional status of participants was evaluated by Hospital Anxiety and Depression Scale (HADS) and Perceived Stress Scale-10 (PSS-10). Statistical analysis was carried out using the software package Statistica 10.0 (StatSoft Inc).Results. Among men, a significantly higher percentage of patients with overweight (body mass index ≥25 kg/m2), higher blood pressure (BP), higher level of cholesterol, and smoking were recorded. Among women, a higher percentage of patients with tachycardia, a sedentary lifestyle, impaired sleep quality and falling asleep were recorded. Sleep duration in young women was significantly lower, and the level of anxiety, depression and stress were higher compared to men. Significant relationships between gender and psychological factors have been identified. Among women, correlations of psychological factors with such parameters as heart rate, total cholesterol, falling asleep and sleep quality were revealed. Among men, significant correlations of anxiety with increased BP, stress and exercise, as well as the presence of cardiovascular diseases in the father were revealed.Conclusion. Gender specificities of RF were revealed: among men — higher frequency of metabolic disorders and higher blood pressure, and among women — psychological factors and low physical activity. It is reasonable to take they into account when developing and implementing individual diagnostic, treatment and prophylactic measures in students.